Complex Janus MoSSe Nanoscrolls Spontaneously Formed from Flat Nanoflakes: A Theoretical Exploration - Ruhao Yang; Han Ye; Qi Wang; Yumin Liu; Wenjun Liu; Zhenping Wu (Small Structures, 2025)
Janus transition metal dichalcogenide (TMD) monolayers with out‐of‐plane atomic asymmetry have been experimentally observed to scroll into unique 1D nanoscrolls with diverse complex structures, while the underlying mechanism has not been unveiled. In this work, the entire scrolling process of triangular and hexagonal MoSSe nanoflakes is successfully simulated based on molecular dynamics, demonstrating the formation of five distinct nanoscroll structures. From flat configuration, the nanoflakes are released along typical directions (including edge‐to‐vertex, vertex‐to‐vertex, and vertex‐to‐edge) accounting for the time‐dependent break of van der Waals (vdW) interaction between substrate and nanoflakes. Key structural parameters such as inner radii are found to be closely related to the nanoflake shapes, sizes, and release directions. Additionally, the regions with various layer numbers in nanoscrolls are projected on the flat nanoflakes to demonstrate the local contribution to the vdW stacked multilayer structures. For each nanoflake shape and release direction, the quantitative relations between the area of specific layer number and both inner radius and interlayer distance are obtained. The results provide a fundamental understanding of complex nanoscrolls spontaneously formed from Janus TMD nanoflakes.